2019
DOI: 10.5005/jp-journals-10024-2657
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Literacy and Oral Health Knowledge among 2,263 First-time Pregnant Urban Women: A Cross-sectional Questionnaire Study

Abstract: Aim: The present study aimed to see the oral health literacy rate among first-time pregnant women across 12 corporate hospital setups in the city of Pune, India. Materials and methods: For the survey, the REALD 30 questionnaires were used to assess the adult literacy rate (with 0 being least score and 30 being the highest score) and the knowledge of the participants related to oral health was assessed using a set of 6 questions. The study was carried out for a period of 1 year from January 2018 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In a Canadian study, Yang et al (26) concluded that cultural and social factors were associated with fetal exposure to tobacco smoke, which is somewhat consistent with the results of the present study. Various studies have shown that health literacy is stronger in people with higher education, employment, study, and access to various information (27)(28)(29). The results of regression model analysis showed the inverse negative effect of cultural capital so that with increasing cultural capital, the amount of fetal exposure to tobacco smoke decreased.…”
Section: Discussionmentioning
confidence: 97%
“…In a Canadian study, Yang et al (26) concluded that cultural and social factors were associated with fetal exposure to tobacco smoke, which is somewhat consistent with the results of the present study. Various studies have shown that health literacy is stronger in people with higher education, employment, study, and access to various information (27)(28)(29). The results of regression model analysis showed the inverse negative effect of cultural capital so that with increasing cultural capital, the amount of fetal exposure to tobacco smoke decreased.…”
Section: Discussionmentioning
confidence: 97%
“… 24 Another study on the oral health literacy of 2263 pregnant women suggests that it is necessary to improve the oral health literacy of pregnant women with the help of education. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Oral health literacy was higher among more educated women in our study. Several reports have also emphasized the direct association between oral health literacy and educational level [8, 10,16,19,[32][33][34][35][36]]. Women's ability to understand and use health information during pregnancy is affected by Health literacy [8].…”
Section: Discussionmentioning
confidence: 99%